Morphological Characterization of 10 Hot Pepper Genotipes in Low Altitude Location - Herison, Catur; Surmaini, Ervi; Rustikawati, Rustikawati; Yulian, Yulian (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2018)
Development of high yielding and superior cultivars requires information on characteristic of germplasm will be used. Ten curly-type hot pepper genotypes was grown in a completely randomized design with three replication in a low altitude land to determine their morphological characters and to evaluate genetic relationship among them based on their morphological similarities. The study was conducted in September 2015 until January 2016 in Medan Baru experimental station of Faculty of Agriculture, 15 m above sea level. Observation was conducted on both quantitative and qualitative characters. The results showed that there were not significantly diferent (?=5%) for plant habitus, leaf shape, leaf tip, leaf edge, leaf shape and seed shape. Whereas for quantitative variables of stem diameter, number of fruits per plants and fruit length were significantly different, while for the other variables were not. Cluster analysis with phylogenetic trees in 58% similarity coefficient resulted that the genotypes grouped in to six groups. Group I consisted of genotype LPK and Ferosa, group II Mario, group III was genotype Laris, group IV consisted of genotype Kopay and Romario, group V KH and L Curup, and group VI included genotype Bogota and Sempurna. The Kopay and Romario genotypes have the closest relationship level of 73%, while Local Payakumbuh and Lokal Curup have the farrest relationship with the coefficient of 35%. From the results of the study it can be concluded that Local Payakumbuh and Local genotypes Curup can be used as parents with the highest probability to have high transgresive segregation or highest hybrid vigor. Keywords: morphological characterization, genetic relationship, curly hot pepper